The Role and Mechanism of Metformin in the Treatment of Nervous System Diseases - Hui Li; Ruhui Liu; Junyan Liu; Yi Qu (Biomolecules)
Nervous system diseases represent a significant global burden, affecting approximately 16% of the world’s population and leading to disability and mortality. These conditions, encompassing both central nervous system (CNS) and peripheral nervous system (PNS) disorders, have substantial social and economic impacts. Metformin, a guanidine derivative derived from a plant source, exhibits therapeutic properties in various health conditions such as cancer, aging, immune-related disorders, polycystic ovary syndrome, cardiovascular ailments, and more. Recent studies highlight metformin’s ability to cross the blood–brain barrier, stimulate neurogenesis, and provide beneficial effects in specific neurological disorders through diverse mechanisms. This review discusses the advancements in research on metformin’s role and mechanisms in treating neurological disorders within both the central and peripheral nervous systems, aiming to facilitate further investigation, utilization, and clinical application of metformin in neurology.